Fruit Traits Reflect Adaptation to Dispersers Along a Tropical Elevational Gradient - Hazell, Richard J; Kaina, Graham S; Sam, Katerina; Souto-Vilarós, Daniel; Koagouw, Wulan; Novotny, Vojtech; Peck, Mika R; Stewart, Alan J A (Ecology and evolution, 2025)
Fruit traits have the potential to influence disperser communities and vice versa. Elevational gradients, where functional traits are known to change rapidly with distance, enable the study of these relationships at local scales. In this pilot study, we examine the trends in three fruit traits related to dispersal by frugivores: size, colour and presentation (i.e., location of displayed fruits on the trunk or on the branches) along a 200-2700 m asl rainforest elevation gradient in Papua New Guinea. We found fruit size to be lower at higher elevations. While specific fruit colours showed few significant elevational patterns, colours typically attributed to attracting avian dispersers were more prevalent at higher elevations. The proportion of ramiflorous species (bearing fruits from branches) increased with elevation. Finally, we use phylogenetic information to test the 'dispersal syndromes' hypothesis: that combinations of fruit traits have evolved in accordance with the preferences and sensory abilities of different frugivore guilds. All fruit traits except presentation showed little evidence of phylogenetic signal but we found fruits displaying colours attributed to attracting mammalian dispersers to be larger than 'bird colour' fruits. We found evidence for the correlated evolution of fruit size and colour, in support of the dispersal syndromes hypothesis. We encourage research at larger scales of time and space to further explore the relationships between fruit traits and frugivores, across elevational and other ecological gradients.
Keywords: frugivory; elevation; phylogeny; gape limitation; dispersal syndromes; fruit traits